Trends in trhee 2003/2004 journalism academic meetings - Meditsch, Eduardo; Segala, Mariana (Brazilian journalism research, 2005)
This paper provides a report of the consolidation of journalism studies in Brazil. It reviews the pieces of research reported in 263 papers presented in six national conferences in 2003 and 2004, according to topic, region, media, quotations, national and disciplinary sources, and type of investigation. The paper concludes that there is a prevalence of studies on approaches, formats and newsmaking, local and national interest, the press and the Internet. The paper also classiﬁ es quotations of authors from Brazil, France and the United States in the ﬁelds of Journalism, Communication studies and Sociology.